THE ROLE OF TEACHERS IN CONDUCTING ASSESSMENTS OF THE LANGUAGE DEVELOPMENT OF 4-5 YEAR-OLD CHILDREN AT TIRTAYASA ISLAMIC KINDERGARTEN - Pika Mariama; Kristiana Maryani; Tri Sayekti (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2026)
Language development assessment in early childhood often faces challenges of objectivity, due to children's behavior in the classroom being difficult to predict. This condition requires teachers to have a deep understanding of how to carry out assessments properly. This study aims to describe the role of teachers in planning, implementing, analyzing, providing feedback, and evaluating, while simultaneously addressing real challenges in conducting language development assessments for children aged 4-5 years at TK Islam Tirtayasa. Through a descriptive qualitative approach, data were comprehensively collected using observation techniques, in-depth interviews with class teachers, and field documentation in the form of checklists, anecdotes, and the work results of Group A children. The data analysis used is based on Miles and Huberman, which includes data reduction, data display, and drawing conclusions. The research results show that Group A teachers have systematically implemented language development assessments through several stages. Nevertheless, in carrying out the effectiveness and consistency of these assessments, teachers sometimes face challenges, namely less conducive classroom conditions, such as children running around, fighting, and crying. This study provides new findings on the contribution regarding the importance of aligning the ability to conduct assessments with teachers' skills in classroom management to maintain the accuracy of assessment results on early childhood language development.